DAMPAK POLA TANAM KOPI TERHADAP PENDAPATAN PETANI (SUATU KASUS DI DESA PULOSARI, KECAMATAN PANGALENGAN, BANDUNG) - Tuti Karyani; Karl Andhika Mahaputra; Endah Djuwendah; Kuswarini Kusno (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Coffee is a plantation commodity that is favored by farmers in Pulosari Village who were initially used to farming vegetables. However, along with the intensification of socialization and the existence of Perhutani's policy through the PHBM concept, public awareness has increased that growing vegetables in a certain slope can damage the soil structure and be counter-productive with environmental conservation. This awareness can be seen from farmers who have dared to switch to monoculture coffee farming, although in fact there are farmers who still farm coffee with polyculture cropping patterns. The research method used was a survey, using different test analysis techniques and descriptive analysis. Thus the purpose of this study was to analyze the impact of monoculture and polyculture cropping patterns on farmers' income and the factors affecting the selection of cropping patterns by coffee farmers. The results of this study show that monoculture coffee farm income is higher than polyculture coffee farming, but when calculated with vegetable crops as intercropping, overall farm income is higher with coffee with intercropping plants even though the costs and risks are also high. The factors that influence the selection of monoculture coffee planting patterns are because the price of coffee is stable, easier to maintain and complies with Perhutani regulations. As for farmers who choose polyculture cropping patterns with vegetables because farmers are already skilled at farming vegetables and the harvest time is faster than coffee.